MEMBANGUN SMART APARATUR SIPIL NEGARA (ASN) MELALUI PELATIHAN - Aan Nopriandi (Balai Diklat Keagamaan Palembang, 2022)
This study aims to examine the development of state civil apparatus (ASN) resources through training in building Smart ASN towards bureaucratic reform. In this study, the method used is